Upper blepharoplasty: A comparative study between wound closure strips and subcuticular closure - Othman Sheriff, Hemin; Raheem Qader, Ari; Hassan M. Ameen, Avan (Kurdistan Journal of Applied Research, 2019)
The objective is to compare the results of patients having their upper blepharoplasty incision closed by subcuticular suturing versus the usage of wound closure strips (Omnistrips®). Also evaluating the time required for incision closure, any complication, and the aesthetic outcome of each technique. In this study a total of 54 upper blepharoplasty had been performed on 27 patients. Retrospective study done on 16 patients, whom incision closure done by continuous subcuticular non-absorbable suture using 6-0 polypropylene (prolene), and another 11 patients prospectively studied for using omnistrips for their blepharoplasty incision closure. The intraoperative time which was required to finish the closure was one of the most important parameter of the study. The other parameters were the incidence of milia occurrence, presence of pain postoperatively at time of stitch and omnistrips removal, infection rate and suture acceptance. The result of this study indicated that mean time of closure was 12.36 minutes with usage of steristrips and (16.88) minutes with subcuticular suturing (P<0.01). The incidence of milia was significantly reduced by using the omnistrips (P 0.004), and there was no pain encountered at time of omnistrips removal in all patients, while all other patients whom subcuticular suturing done for them complained of pain at the time of stitch removal. The study showed no infection associated with closure of the incision in either groups. In conclusion the closure of the incision in upper lid blepharoplasty using omnistrips is a safe, effective, faster, painless and with less complication rate than that using subcuticular suturing technique.